THE NATIONAL AND POLITICAL MISSION OF FRA GRGUR–GRGO ŠKARIĆ (1831–1876): FOR THE PUBLIC GOOD OF THE SERBIAN NATION - Teinović, Bratislav (National interest, 2024)
Fra Grgur–Grgo Škarić is one of the most secretive historical figures of the political life in Bosnia and Herzegovina during the 1860/70s. Škarić was born on July 13, 1831 in Županjac (formerly Duvno, now Tomislavgrad) in west Herzegovina where, according to Škarić himself, “the Serbs–Catholics reside“. He completed the elementary education at the Franciscan school in Čerigaj near Široki Brijeg. At that time he changed the name Jure that he was given at birth to Grgur–Grgo. He graduated the Franciscan theology and philosophy in Venice. As a professor at the Catholic seminary in Široki Brijeg (1866–1869), he taught his students the Serbian national spirit, swearing them “for the public good of the Serbian nation“. The pressure he was exposed to due to the national mission he was leading and suspicions that he was preparing an uprising, forced him to defect in the autumn of 1869 to the Principality of Serbia, where he received citizenship and financial aid from its government. The Serbian regent Jovan Ristić was the patron of Škarić’s plan to launch the “Society of Roman Catholic Youth in Herzegovina“, which had the main tasks of eradicating the hatred of the Catholics towards the Orthodox, awakening among the Catholics the spirit of Serbian nationality and the idea of liberation, assuring Catholics that they were of the Orthodox faith until the 14th century and that the word Serb does not mean religion, but nationality. While in Belgrade, he worked closely with Serbian governmentʼs top three people in charge of conspiratorial activities in Bosnia and Herzegovina: Nićifor Dučić, Niko Jovanović Okan and Gavro Vučković–Krajišnik. Under the name of “Jova Kosanović“, he worked for the Serbian ministry of foreign affairs until the January 1, 1873, as an agent and representative of the “Catholic element of Bosnia and Herzegovina“. For the next two years he was preparing the uprising in his homeland of western Herzegovina, writing about it in a letter to his friends Fra Ilija Lekić and Fra Antun Vladić in 1875 and giving his opinion on the political future of the most western Turkish province in Europe. Škarić left the uprising in which he was actively involved from the first day in the vicinity of Ljubuški, for an unknown reason. He also ended his life in a mysterious way at the end of 1876 in Zagreb, where he was buried the same year. The first part of the paper, after a brief biography of Škarić, discusses his conspiratorial work at the seminary in Široki Brijeg and in Belgrade and in the second part, four of his documents are analysed and discussed: “Memorandum“ to Ristić and the Serbian Regency (November 1869), “Plan and Advice“ for the national emancipation of Catholics (and Muslims) in Bosnia and Herzegovina (December 1869), a Proposal for an agreement on the cooperation of Catholics in Western Herzegovina with the Serbian Regency (June 1870) and a letter of protest and advice to friend in Mostar, the secretary of the Austrophile bishop of Herzegovina, Fra Ilija Lekić (November 1875).